Agronomic performance of Raphanus sativus L. cultivars grown under different spacings - Alvim, Jorgeana Francis; Lopes Sobrinho, Oswaldo; Cantanhede, Erika Kássia; Pereira, Alvaro Itaúna; Silva, Valdelânia; Santos, Leonardo (Revista de Ciencias Agrícolas, 2020)
An ideal spacing between plants should be established for the optimization of radish (Raphanus sativus L.) crops since the plant spatial distribution of plants affects the crop yield. This study was conducted aiming to evaluate the agronomic performance of radish cultivars grown under different spacings. The experiment was conducted at the Experimental Field of the Federal Institute of Education, Science, and Technology of Maranhão, in Codó, MA, Brazil, from June to July 2017. The experiment was conducted in a randomized block design with five replications, using a 2×2 factorial arrangement. The factors consisted of 2 cultivars (Sparkler Ponta Branca and Saxa) and 2 spacings between plants (5 and 8cm), totaling 20 experimental plots. Data were collected in 6 plants from each experimental plot. The agronomic parameters: total fresh weight (TFW), root fresh weight (RFW), root mean diameter (RMD), root means length (RML), and root yield (RY) of the radish plants were evaluated. The factors (cultivars and spacing between plants) had no significant effect on TFW, RFW, RML, and RMD. The spacing between plants has a significant effect on the yield of radish crops of the cultivar Saxa, and higher yields are found when using the spacing of 5cm.